Trace elements bioaccumulation in Porcellionides pruinosus (Brandt, 1833) and related biomarkers of exposure. Issue 6 (14th January 2019) - Droutsa, Angeliki; Emmanouil, Nikolaos; Raptopoulos, Konstantinos; Salvaggio, Antonio; Mazzei, Veronica; Pecoraro, Roberta; Messina, Giuseppina; Copat, Chiara; Ferrante, Margherita; Brundo, Maria Violetta; Lombardo, Bianca Maria
Abstract: In the last years, the increase of anthropogenic activities has led to a progressive pollution of ecosystems. Oniscidean isopods are a group of terrestrial animals known as excellent bio‐indicators and bio‐accumulators, because of their capacity to accumulate contaminants and to implement appropriate strategies of detoxification. For this study, we collected Porcellionides pruinosus from two different sites in the Corinth region (Greece), a polluted site and a control site, to assess the heavy metal pollution status. We conducted an inductively coupled plasma mass spectrometry (ICP‐MS) analysis for the detection of trace elements in animals' hepatopancreas and soil; we performed also immunohistochemistry for detection of metallothioneins 1 (MT1) and heat shock protein 70 (HSP70s). The results suggest a great capacity of the species in trace elements bioaccumulation and the high degree of pollution of the area near Agioi Theodoroi where the metal pollution index (MPI) is threefolds higher than the control site, due to the presence of significantly higher concentration of arsenic, cadmium, cobalt, chromium, manganese, molybdenum, and lead found in hepatopancreas and soil. The environmental stress is confirmed by the expression of the relative biomarkers of exposure MT1 and HSP70. Our study, with a multimarker approach, consents getting a complete analysis of environmental quality and the effect of pollution on organisms and shows for the first time the heavy metals contamination status in certain Greece area. Furthermore, P. pruinosus proved to be an appropriate indicator of pollution in terrestrial ecosystems. Abstract : A great capacity of Porcellionides pruinosus to accumulate trace elements. Isopods might be useful as bioindicators of soil contamination. The environmental stress is confirmed by the expression of biomarkers of exposure MT1 and HSP70.